Invisible Theatre: militarized space and the staging of affective atmospheres - Leah Lovett (Ambiances)
This paper revisits the circumstances surrounding Brazilian theatre director, Augusto Boal’s first recorded experiment with Invisible Theatre in a restaurant in Buenos Aires (1972) in light of Anderson’s (2014) theory of affective atmospheres in their capacity to mediate structures of feeling. Drawing on original archival and performance-based research, I advance a critical account of Restaurant Theatre: The Law through a narrative reimagining of the performance and key evidence concerning the law in question that fundamentally challenges Boal’s claims for the technique as a means of social liberation from forces of oppression. The alternative possibility explored here is that Invisible Theatre developed in Boal’s practice as an atmospheric reaction to militaristic forms of urban encounter and a means with which to infiltrate structural feelings of fear. This idea is traced through Boal’s encounters with state apparatus of affective control as a political prisoner and marked dissident in exile, and with the performative concept of camouflage. Freed from the overdetermining binaries of oppressor and oppressed, I suggest Invisible Theatre can open up opportunities for practitioners seeking to stage affective atmospheres to produce transformative encounters and perceptions.